2022
DOI: 10.1021/acs.jpcc.2c03256
|View full text |Cite
|
Sign up to set email alerts
|

Performance Upper Limit of Sub-10 nm Monolayer MoS2Transistors with MoS2–Mo Electrodes

Abstract: Field-effect transistors (FETs) fabricated with monolayer (ML) molybdenum disulfide (MoS 2 ) exhibit great potential as a promising candidate for next-generation nanoelectronic devices. However, the practical application of ML-MoS 2 -based transistors is severely restricted by the high contact resistance and poor current-delivery capability between the common metals and ML-MoS 2 at present. Here, through the systematical screening of the contact performance between metals (Sc, In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The n-type and p-type SBHs can be extracted from the projected band structures of MoS 2 -metal-close and -vdW interfaces, which are illustrated in the upper and lower panels of Figure 2, respectively. It can be observed that the Fermi level is closer to that of the CBM, indicating that the n-type Schottky contacts are formed in all 1L MoS 2 -metal close interfaces due to the strong FLP, which are in agreement with previous reports [54,55]. For 1L MoS 2 -metal vdW interfaces, MoS 2 -Al (or Ag, Cu, Au, or Pd) still preserves the n-type Schottky contacts.…”
Section: Sbh Of 1l Mos 2 -Metal-close and -Vdw Interfacessupporting
confidence: 90%
“…The n-type and p-type SBHs can be extracted from the projected band structures of MoS 2 -metal-close and -vdW interfaces, which are illustrated in the upper and lower panels of Figure 2, respectively. It can be observed that the Fermi level is closer to that of the CBM, indicating that the n-type Schottky contacts are formed in all 1L MoS 2 -metal close interfaces due to the strong FLP, which are in agreement with previous reports [54,55]. For 1L MoS 2 -metal vdW interfaces, MoS 2 -Al (or Ag, Cu, Au, or Pd) still preserves the n-type Schottky contacts.…”
Section: Sbh Of 1l Mos 2 -Metal-close and -Vdw Interfacessupporting
confidence: 90%
“…Similar results have also been found in MoS 2 based MSJs. [48] To further understand the interface properties, we constructed a two-probe CrX 2 N 4 based FET device model with a channel length of 5 nm, as illustrated in Figure 3. The injection of carriers in the studied CrX 2 N 4 based FETs involves two representative interfaces: the interface B between the metal electrode A and the bottom CrX 2 N 4 region C, and the interface D between the source/drain region and channel region E. The CrX 2 N 4 based FETs contain vertical and lateral Schottky barriers in the interface B and D, which represent the energy barriers that need to be overcame for carriers to inject from the metal into the underlying CrX 2 N 4 monolayer (from A to C in Figure 3) and the source/drain into the channel (from C to E in Figure 3), as expressed as Φ V and Φ L , respectively.…”
mentioning
confidence: 99%